Response of Okra (Abelmoschus esculentus L.) to Growth Regulators and Organic Manures - Chowdhury, M S; Hasan, Z; Kabir, K; Jahan, M Shah; Kabir, M H (The Agriculturists, 2015)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> A study was conducted at the Horticulture Farm, Sher-e-Bangla Agricultural University, Bangladesh during April to September, 2012 to determine the suitability of selected plant growth regulators and the proper use and effectiveness of selected organic manures and also their suitable combinations for successful okra production. The experiment consisted of two factors: factor A: growth regulators as - G0: control (water), G1: GA3 (100 ppm) and G2: Miraculan (1000 ppm) and factor B: organic manures as - OM0: control (no manure), OM1: vermicompost (9 t/ha) and OM2: poultry manure (11.5 t/ha). The combined use of GA3 and poultry manure produced the tallest plants. Both the growth regulators and organic manures enhanced early flowering. In case of growth hormone, the highest yield (16.67 t/ha) was recorded from G1 followed by G2 (16.49 t/ha). The highest yield (18.03 t/ha) was found from OM2, closely followed by OM1 (17.59 t/h). Considering the treatment combinations, the highest yield was harvested from G1OM2 (19.62 t/ha), followed by G1OM1 (19.01 t/h), G2OM1 (18.42 t/h) and G2OM2 (18.30 t/h), respectively. <span style="font-size: 12.0pt; font-family: 'Calibri','sans-serif'; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: 'Times New Roman'; mso-fareast-theme-font: minor-fareast; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The Agriculturists <span style="font-size: 12.0pt; font-family: 'Calibri','sans-serif'; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: 'Times New Roman'; mso-fareast-theme-font: minor-fareast; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">2014; 12(2) <span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: 'Times New Roman'; mso-fareast-theme-font: minor-fareast; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">56<span style="font-size: 12.0pt; font-family: 'Calibri','sans-serif'; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: 'Times New Roman'; mso-fareast-theme-font: minor-fareast; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">-<span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: 'Times New Roman'; mso-fareast-theme-font: minor-fareast; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">63 <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>